Reparameterization of Ruled Surfaces: Toward Generating Smooth Jerk-minimized Toolpaths for Multi-axis Flank CNC Milling. (October 2020) - Hashemian, Ali; Bo, Pengbo; Bartoň, Michael
Abstract: This paper presents a novel jerk minimization algorithm in the context of multi-axis flank CNC machining. The toolpath of the milling axis in a flank milling process, a ruled surface, is reparameterized by a B-spline function, whose control points and knot vector are unknowns in an optimization-based framework. The total jerk of the tool's motion is minimized, implying the tool is moving as smooth as possible, without changing the geometry of the given toolpath. Our initialization stage stems from measuring the ruling distance metric (RDM) of the ruled surface. We show on several examples that this initialization reliably finds close initial guesses of jerk-minimizers and is also computationally efficient. The applicability of the presented approach is illustrated by some practical case studies. Graphical abstract: Highlights: We present a novel jerk minimization algorithm for multi-axis flank CNC machining. The toolpath of the milling axis is reparameterized by a B-spline function. The jerk of the motion is optimized without changing the geometry of the toolpath. Our initialization stems from measuring the ruling distance metric of the toolpath. The applicability of the presented method is illustrated by several case studies.